THE IMPACT OF LEADERSHIP AND INCENTIVES ON EMPLOYEE PERFORMANCE AT THE DEPARTMENT OF FOOD SECURITY, FOOD CROPS AND HORTICULTURE, LAMPUNG PROVINCE - Aprinis . (University of Sang Bumi Ruwa Jurai, 2021)
. This study aims to examine the effect of incentives and leadership on employee performance at the Department of Food Security, Food Crops and Horticulture, Lampung Province. This study uses a sampling research method with the number of respondents as many as 88 employees. The analysis used quantitative analysis and data processing using SPSS program. The results showed that incentives have a positive effect on employee performance with a contribution of 47.1% influence. Furthermore, leadership also has a positive effect on employee performance with an influence contribution of 44.3%. Regression test shows that together there is a positive influence between incentives and leadership on employee performance. The magnitude of the influence of the two variables X1 and X2 on Y is 56.7%, the remaining 43.3% is influenced by other variables outside.